Development of a Rapid UPLC Method for Analysis of Carotenoids in Goji Berry Extract and Evaluation of Their Transformation Affected by Saponification - Bo-Yang Hsu; Chia-Hui Lin; Tsai-Hua Kao (Molecules)
Goji berry (Lycium barbarum L.), also known as wolfberry, is a traditional Chinese medicinal herb widely utilized as a functional food ingredient throughout East Asia. In this study, we developed a rapid high performance liquid chromatography-diode array detection (HPLC-DAD) method for the simultaneous separation of carotenoids in goji berries. This method successfully separates 17 carotenoids and their esters within 21 min using a Sunrise C30 column, with detection at 450 nm, a flow rate of 1.3 mL/min, and a column temperature of 25 °C. Method validation showed intra-day precision ranging from 0.97% to 6.21% and inter-day precision from 0.99% to 7.01%, demonstrating this method effectively minimizes analysis time while providing high separation efficiency and sensitivity. Goji berries extracted with a mixture of n-hexane/ethanol/acetone (1:1:1, v/v/v) and then saponified with a 40% potassium hydroxide methanol solution can completely convert carotenoid esters into free monomer forms. The highest carotenoid content in goji berry was all-trans-zeaxanthin (1721.94 ± 81.01 μg/g), followed by 9- or 9′-cis-zeaxanthin (79.53 ± 3.92 μg/g), 15- or 15′-cis-zeaxanthin (43.71 ± 2.17 μg/g), 9- or 9′-cis-zeaxanthin (36.51 ± 1.81 μg/g), all-trans-β-cryptoxanthin (25.76 ± 1.55 μg/g), all-trans-β-carotene (5.71 ± 0.83 μg/g), and 13- or 13′-cis-β-carotene (0.86 ± 0.13 μg/g).